EPISTEMOLOGI PEMIKIRAN FRED McGRAW DONNER TENTANG HISTORISITAS AL-QUR’AN - Poipesi, sahrul (Jurnal Studi Islam, 2025)
Various criticisms of the historicity of the Qur'an have been raised in the Western world by some orientalists who consider the historical value of the Qur'an has been lost since the codification. Fred McGraw Donner offers a more thorough reading based on the historicity of the Qur'an. This research aims to answer three problems. First, it reveals the forms of the study of the historicity of the Qur'an from Fred M. Donner. Second, discussing the factors that encourage the study of the historicity of the Qur'an. Third, revealing the implications of the study of historicity on the understanding of the Qur'an. The method used in this research is qualitative-descriptive, the results of this study indicate that there are three forms or procedures that can be considered as methods for studying the historicity of the Qur'an, namely starting from the text of the Qur'an, comparing the instructions from the Qur'an with historical literature and the last to see the phenomenon of religion in the near east in the last antique period. In addition, the driving factor that led to the birth of the study of the historicity of the Qur'an was motivated by the development and trend of non-Muslim Qur'anic studies in the West from the 19th century to the 20th century. Then the implications that result from the study of the historicity of the Qur'an will have an impact on individuals, society and educational institutions. Keywords: Epistemology, Historicity of the Qur'an, Fred McGraw Donner